Analysis on Smoking Behavior of Final Semester Students of Diponegoro University Semarang - Pramita, Tiara Hasna Widya; Prabamurti, Priyadi Nugraha; Handayani, Novia (Journal of Public Health for Tropical and Coastal Region, 2025)
Introduction: World Health Organization (WHO) data showed that tobacco consumption causes millions of deaths each year. Research on the University of Riau students found that 22-year-old students, who worked on their theses, tended to smoke. Another study at Faculty of Medicine, Diponegoro University, showed that college students used cigarettes to cope with academic stress. This study aimed to determine factors associated to smoking behavior on final-semester students of Diponegoro University Semarang.Methods: This observational study used a cross-sectional design. The purposive sampling with the criteria of Undip students who were active members of Thesis World Community, X social media accounts who were working on their thesis on May-August 2024, on the 2018-2020 class who smoked, and agreed to fill out the research forms. This study included a total of 100 students. Data collection was conducted through gforms, disseminated online in the Thesis World Community. Data analysis was performed using the chi-square tests.Results: These variables were associated to light or heavy smoking behavior: father's education level (p=0.004), mother’s education level (p=0.001), knowledge about the dangers of smoking (p=0.003), family encouragement (p=0.001), peer encouragement (p=0.011), perceived vulnerability (p=0.001), perceived seriousness (p=0.020), perceived benefits (p=0.022), perceived barriers (p=0.001), suggestions from others (p=0.001), and family experience (p=0.032). The variables that had no association with heavy smoking behavior were age (p=0.394) and sex (p=0.796).Conclusion: The determinants associated with heavy students' smoking behavior were low parental education level, the dangers’ of smoking knowledge, family encouragement, peer encouragement, perceived vulnerability, perceived seriousness, perceived benefits, perceived barriers, advice from others, and family experience.